Editorial - Vieira, Wilson; Cepêda, Vera Alves; de Malta, Maria Mello (Cadernos do Desenvolvimento, 2022)
Editorial. Cadernos do Desenvolvimento, Centro Celso Furtado, Rio de Janeiro, v. 16, n. 30, p. 7-8, set.-dez. 2021.